2016
DOI: 10.1111/jocn.13299
|View full text |Cite
|
Sign up to set email alerts
|

An integrative review of the factors related to building age‐friendly rural communities

Abstract: It is important for nurses, working in primary health care settings, to understand the needs of older people in the communities in which they practice. This includes the community characteristics that can be enablers and barriers to older people being able to remain and age within their own communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Migration to continuum care communities is presenting a new challenge for care providers to prevent infection within the communities (Neville et al, 2016;Hertz, 2015. ) To ensure high-quality care, a focus on appropriate use of antibiotics will prevent negative healthcare outcomes in the new healthcare communities (Neville et al, 2016;Hertz, 2015;Van de Berg et al, 2015).…”
Section: Impact On Qualitymentioning
confidence: 99%
“…Migration to continuum care communities is presenting a new challenge for care providers to prevent infection within the communities (Neville et al, 2016;Hertz, 2015. ) To ensure high-quality care, a focus on appropriate use of antibiotics will prevent negative healthcare outcomes in the new healthcare communities (Neville et al, 2016;Hertz, 2015;Van de Berg et al, 2015).…”
Section: Impact On Qualitymentioning
confidence: 99%
“…Age-friendly environmental factors that may have some influence in health results: Several factors that may hinder health care of the elderly have been found related to physical difficulties in accessing to the health centers, in their structure and in the transmission of information. [9][10][11][12] However, the available scientific evidence, which is very limited, does not allow generating reasonably firm conclusions. There are some elements that a health center that seeks to be agefriendly has to consider.…”
Section: Principal Topicsmentioning
confidence: 99%
“…These include accessibility from the patient's home to the health center, distance, means of transport, state of the roads and sidewalks and architectural barriers (stairs, ramps, curbs, etc.). [9][10][11][12] In many cases, these elements do not depend directly on the primary health care center but in local administrations. The association found between improvement in health and decrease in mortality in the cities with the largest number of green areas 10 is striking.…”
Section: Principal Topicsmentioning
confidence: 99%
“…The demographic characteristics of rural populations are changing, and as a result rural populations, particularly those in the western world, are typically older in comparison with urban areas (Neville, Napier, Adams, Wham, & Jackson, 2016). This can be partially explained by an exodus of younger people to cities in search of employment and an associated inward migration of older people to rural areas owing to their affordability, as well as for lifestyle choices and the desire to reconnect with rural roots (Stockdale, 2011; Vuin, Carson, Carson, & Garrett, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…By doing so social participation is fostered and supported (Neville, Napier, et al, 2016). Research has shown that rural communities with high walkability are associated with independence and increased social interactions (Bacsu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%